(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
Child Sexual Abuse (CSA) is one of the prevalent problems in the global world. It is an all- encompassing communal and collective distress that can affect members of the society directly or indirectly, and particularly, the victims’ welfare and efficiency throughout their existence. Thus, this study investigated the socio-cultural context of child sexual abuse and identified the coping strategies adopted by the victims of child sexual abuse in South-South, Nigeria. Primary data were adopted for this study. Information were sourced using both questionnaire and interview tools. 1012 respondents, who were adolescents (Senior Secondary School students of 11-18 years) and adult police officers, non-governmental organization workers and health professionals, were engaged in the study area. Majority (59.7%) of which were female, while male respondents accounted for 40.3%. Both descriptive and inference techniques were employed to analyse the data. The findings revealed that 85.3% of the respondents stated that their culture does not allow/permit child marriage. Also, 69.6% of the respondents affirmed that their culture allows the practice of polygamy family system. However, 15.3% of the respondents stated that polygamy is not fostered by their culture. Also, from the table, the majority of the respondents going by 65.7% stated that their culture frown at child marriage, while another majority going by 89.7 % stated that their culture allows/permit premarital sex. The coping strategies adopted significantly influence the victims of child sexual abuse (child support institution/hospital/rehabilitation center, receiving counseling from parent/guardian, counseling and routine checkups, and rehabilitation activities, physical and emotional support). This study recommends enlightening initiatives in schools, religious centers and homes with a view to impacting the children with skills and knowledge to help them recognize unsafe situation and prevent sexual abuse such as identifying limit violations, superfluous forms of touching and how to beckon or call for help. Also, there should be concentrated impact of post-disclosure events on victims – the investigation, justice processes and publicity. In addition, government should lead on securing better and more consistent support for victims of child sexual abuse through entire court processes and beyond into therapeutic support for victims of child sexual abuse.